EFFECT OF FOOT POSTURE AND FATIGUE ON STATIC BALANCE AND ELECTROMYOGRAFIC ACTIVITY OF SELECTED LOWER LIMN MUSCLES - Adriyani, Riza
Background and Objective : An efficient foot posture is needed to stabilize ankle joint. Fatigue could lead to excessive eversion of subtalar joint and affect static balance. Higher muscle activity is needed to stabilize tarsal tranversal and subtalar joint in order to reduce load on medial longitudinal arch, this will caused muscle fatigue and pain earlier in flatfoot compared to normal foot children. Therefore, this study was aimed to find out the effect of foot posture and jumping fatiguing effect on static balance and muscle activity of selected lower limb muscles in school children. Methods : 19 elementary and 30 junior high school children aged 9 to 14 years took part in this study. Of these all children, 25 had normal foot (16 males and 9 females) and 24 had flatfoot (11 males and 13 females) which was classified into flatfoot and normal foot groups. Foot posture was classified based on arch index of footprint by a foot scanner which calculated the data using AUTOCAD 2013 software. Surface electromyography (EMG) activity was recorded from tibialis anterior, gastrocnemius medialis and peroneus longus muscles while those participants were standing on one leg barefoot with opened eyes. All participants completed the entire protocol (pre fatigue data collection, fatigue protocol, and post fatigue data collection) in a single session. Static balance and electromiographic data were collected before and after a functional fatigue protocol. Results : School children with normal foot had arch index 0.25±0.01 whereas those with flatfoot had 0.36±0.01. In fact, there were no significant differences for anthropometric characteristics between children with flatfoot and normal foot. This statistical analysis showed that fatigue could influence static balance in flatfoot school children (p < 0.05), but not in normal foot school children. Based on electromiographic data, the statistical analysis showed that there were significant differences (p < 0.05) of the decreased median frequency on tibialis anterior in flatfoot compared to normal foot school children after fatigue. However, there were no significant differences on median frequency of gastrocnemius medialis and peroneus longus between both groups. After fatigue, median frequency timing was significantly different (p < 0.05) on tibialis anterior and peroneus longus in flatfoot compared to normal foot children and tended to appear earlier on tibialis anterior, gastrocnemius medialis and peroneus longus in flatfoot compared to normal foot. Conclusion : Fatigue influenced static balance and tended to appear earlier on selected lower limb muscles while performing static balance in flatfoot school children. After fatigue, median frequency decreased (tremor) showed more significant differences on tibialis anterior in flatfoot rather than in normal foot school children.